2021
DOI: 10.1186/s12864-021-07796-8
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing reveals transcriptomic changes in tobacco (Nicotiana tabacum) following NtCPS2 knockdown

Abstract: Background Amber-like compounds form in tobacco (Nicotiana tabacum) during leaf curing and impact aromatic quality. In particular, cis-abienol, a polycyclic labdane-related diterpenoid, is of research interest as a precursor of these compounds. Glandular trichome cells specifically express copalyl diphosphate synthase (NtCPS2) at high levels in tobacco, which, together with NtABS, are major regulators of cis-abienol biosynthesis in tobacco. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…During tobacco leaf curing, Cembratriene-diol (CBT-diol) is degraded to produce solanone, solanofuran, solandione, and other flavor components. The degradation products of cis-abienol are mainly C-16 compounds, including ambroxide and ambreinolide, and other substances that have a strong ambergris (cypress wood) aroma [5]. Menetrez et al [6] were the first to find that α-CBT-diol and β-CBT-diol have strong inhibitory effects on conidial germination…”
Section: Introductionmentioning
confidence: 99%
“…During tobacco leaf curing, Cembratriene-diol (CBT-diol) is degraded to produce solanone, solanofuran, solandione, and other flavor components. The degradation products of cis-abienol are mainly C-16 compounds, including ambroxide and ambreinolide, and other substances that have a strong ambergris (cypress wood) aroma [5]. Menetrez et al [6] were the first to find that α-CBT-diol and β-CBT-diol have strong inhibitory effects on conidial germination…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we performed transcriptome analyses of tobacco plants with cis -abienol synthesis gene NtCPS2 knockdown and studied their physiology and biochemistry characteristics ( He et al., 2021a ; He et al., 2021b ). We found that knocking down the cis -abienol synthesis gene NtCPS2 not only reduced the relative expression of NtCPS2 gene and the content of cis -abienol, but also affected related genes in the GA synthesis pathway, thus increasing the GA content.…”
Section: Introductionmentioning
confidence: 99%